2020
DOI: 10.3390/cryst10111002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization on the Surface of Copper Sulfide Minerals Probed by Fourier Transform Infrared Micro-Spectroscopy

Abstract: Biofilm formation is a molecular assembly process occurring at interfaces, such as in bioleaching processes. The real time monitoring of the marker bands of amide I/amide II by FTIR microspectroscopy during Acidithiobacillus ferrooxidans colonization on chalcopyrite surfaces revealed the central role of lipids, proteins and nucleic acids in bacterial cell attachment to copper sulfide surfaces. The Raman and FTIR spectra of the interactions of Acidithiobacillus ferrooxidans with bornite are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Moreover, the FTIR spectrum of the Gelidium corneum biomass before the bio-adsorption process shown a characteristic absorption band at ν = 1642 cm −1 owing to amidic carbonyl (C=O) or strong C=C stretching as reported by Di et al 76 . The absorption band at ν = 1542 cm −1 is attributed to the C=C stretching or amide-II (protein N–H bend, or C–N stretch) Varotsis et al 77 . Karar et al 78 , have reported the absorption band related to CH 2 -bending vibrations of the methyl group; lipids and proteins at ν = 1447 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the FTIR spectrum of the Gelidium corneum biomass before the bio-adsorption process shown a characteristic absorption band at ν = 1642 cm −1 owing to amidic carbonyl (C=O) or strong C=C stretching as reported by Di et al 76 . The absorption band at ν = 1542 cm −1 is attributed to the C=C stretching or amide-II (protein N–H bend, or C–N stretch) Varotsis et al 77 . Karar et al 78 , have reported the absorption band related to CH 2 -bending vibrations of the methyl group; lipids and proteins at ν = 1447 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The study shows that genetical control mechanisms of bacteria and fungi regulate the size and shape of the nanoparticles as well as the number of nanoparticles secreted by the microorganisms. The interaction of bacteria with substrate surfaces, marble [2] and copper sulphide [3] is detailed by Sazanova et al The obtained results demonstrate that mineral secretion activity differs significantly for B. subtilis monocultures and B. subtilis-A. niger associations.…”
mentioning
confidence: 99%
“…Furthermore, the study has shown that the phase composition and morphology of the precipitated crystals is influenced by the ratio of bacterial EPS-oxalic acid concentration in the growth medium. Bacterial cell attachment to copper sulphide surfaces was investigated by Varotsis et al [3]. The research documented that the degree of CuS surface colonization by Acidithiobacillus ferrooxidans is mainly dependent on the speciation of the protein within the EPS, followed by nucleic acids and lipids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lipid bilayer vehicles, OMVs, form a part of the lipid content in the biofilm matrix [136] since they relay the exportation of intercellular and membrane proteins, signaling molecules for interspecies communication, toxins, and nucleic acids. Lipid secretion is also important in bacterial attachment onto abiotic or biotic surfaces such as the colonization on copper sulfide minerals by Acidithiobacillus ferrooxidans [137], or intestinal substratum by…”
Section: Lipidsmentioning
confidence: 99%